QUALITY TRAITS OF FRESH, REFRIGERATED AND CRYOPRESERVED BUFFALO BULL SEMEN AND THEIR INTERRELATIONSHIPS - Varghese, Orin; Dhami, AJ; Chaudhari, DV (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A study was carried out on semen ejaculates (40) of five healthy Surti buffalo bulls during favourable breeding season. The ejaculates with >70% IM were diluted @ 100 million sperms/ml in Tris-fructose egg yolk-glycerol (TFYG) diluent supplemented with L-cysteine @ 1 mg/ml, and examined for quality parameters such as sperm progressive motility, viability, morphology, acrosomal and plasma membrane integrity. A part of the extended semen was preserved at 5°C and another was processed for ultra-low temperature (-196°C) preservation in LN2 using biofreezer after filled in French mini straws. The mean values of ejaculate volume, sperm concentration, mass activity (0-5 score), individual sperm motility, live sperm, abnormal sperm, intact acrosome and HOS reactive sperms observed in fresh semen were 3.04±0.11 ml, 963.05±50.97 million/ml, 2.97±0.06, 75.00±0.69 %, 88.22 ±0.48 %, 4.40±0.26 %, 93.67±0.31 % and 89.17±0.57 %, respectively. Just after dilution the percentages of progressively motile, live & abnormal sperms, intact acrosomes and HOS reactive sperms were 80.51±0.65, 85.95±0.65, 4.92±2.20, 91.00±2.30, 85.72±0.67, respectively. The corresponding values after 48 hrs of refrigeration (5°C) were 61.75±0.85, 67.85±0.85, 6.45±0.27, 89.05±0.32, 67.30±0.96%, the values at pre-freeze stage (after equilibration) were 72.62±0.69, 78.97±0.93, 5.45±0.25, 90.90±0.35, 78.12±0.79% and at post-thaw stage (37°C/30 sec) 46.50±0.72, 52.97±0.79, 7.10±0.26, 85.73±0.18, 51.62 ±0.82%, respectively. The mean motile spermatozoa observed after 1, 2 and 3 h of post-thaw incubation at 37°C in water bath were 32.75±0.82, 18.88 ±0.70 and 8.88±0.66% (P<0.01), respectively. The semen quality parameters, fresh and cryopreserved were acceptable for artificial breeding use. The seminal traits in initial, 48 hrs refrigerated, pre-freeze and post-thawed samples revealed significant (p<0.01) interrelationships (r = 0.44 to 0.84) between progressive motile sperm, live sperm and HOST reactive sperm directing more emphasis on these quality parameters for better semen evaluation.